Digital Musical Storytelling to Enhance First-Grade Elementary School Students' Listening Skills - Waluyo Hadi Hadi; Rieska Ramadhani; Arita Marini; Gusti Yarmi; Desy Safitri; Leola Dewiyani (Journal of Education Technology, 2023)
The development of educational technology has become an essential factor in solving academic problems. Educational technology can provide accessible information and delivery of material so that the learning activities carried out do not become a significant obstacle to learning effectiveness. This study aims to analyze the use of digital musical storytelling to increase first-grade elementary school student listening skills. The method used in this research is the experimental method. The research design used in this study was a one-group pretest-posttest design. The population in this study was the first graders of elementary school. Data collection techniques were direct observation and measurement techniques. The data is ana-lyzing statistically using SPSS. The results showed that there is an average difference between pretest and posttest learning outcomes, which means that there is an effect of using digital music storytelling on stu-dents' listening skills. The contribution of this study is to help students learn music courses with more fun and easier understanding.